Emerging human dimensions research in coastal and nearshore Oceania - Rachel Dacks; Shreya Yadav; Alexander Mawyer (Conservation Biology, 2025)
Calls for incorporating human dimensions into marine conservation have increased and begun to coalesce as marine social science. However, it is unclear what types of research and foci have been centered in this new interdisciplinary field and what gaps remain. Seeking to clarify the state of marine social science's emerging discourses and methods, we conducted a systematic mapping review of human dimensions studies in coastal and nearshore Oceania published from 2016 to 2022. We reviewed 684 studies, most of which appeared in interdisciplinary marine science journals. We deductively coded studies using previously established human dimensions categories. Australia, Aotearoa New Zealand, Hawaiʻi, and Fiji were the focus of 65% of studies despite comprising only a fraction of the total region. Emerging themes of the study included Indigenous worldviews, complex and nuanced drivers of human behavior, diverse human–ocean relationships, and social equity and justice. Some of the studies notably complicated common assumptions about human behavior in marine domains. Over half of the studies used mixed methods, engaging multiple perspectives and allowing for a more comprehensive understanding of research domains that may set marine social science apart in its ability to incorporate understudied human dimensions into marine conservation. Participatory methods, although not yet common, provide a valuable suite of approaches to understanding issues of social equity in marine management and studies of sensory and affective dimensions, also uncommon, could be of high value in filling gaps in understanding of people's complex relationships with marine places. Expanding interdisciplinary training for the next generation of marine stewards and transdisciplinary collaborations will provide opportunities to further mainstream marine social science for a richer, more comprehensive, and just understanding of the world's peopled seas.

Microplastics absent from reef fish in the Marshall Islands: Multistage screening methods reduced false positives - Katherine R. Shaw; Jonathan L. Whitney; Eileen M. Nalley; Madeline C. Schmidbauer; Megan J. Donahue; Jesse Black; Raquel N. Corniuk; Kellie Teague; Rachel Sandquist; Catherine Pirkle; Rachel Dacks; Max Sudnovsky; et al. (Marine Pollution Bulletin, 2024)

Post-cyclone resilience of an agroforest-based food system in the Pacific Islands - Ashley McGuigan; Tamara Ticktin; Mesulame Tora; Veniana Tikonavuli; Shimona A. Quazi; Rachel Dacks (Regional Environmental Change, 2022)

Creating a space for place and multidimensional well-being: lessons learned from localizing the SDGs - Eleanor J. Sterling; Puaʻala Pascua; Amanda Sigouin; Nadav Gazit; Lisa Mandle; Erin Betley; John Aini; Simon Albert; Sophie Caillon; Jennifer E. Caselle; Samantha H. Cheng; Joachim Claudet; et al. (Sustainability Science, 2020)
Achieving sustainable development globally requires multilevel and interdisciplinary efforts and perspectives. Global goals shape priorities and actions at multiple scales, creating cascading impacts realized at the local level through the direction of financial resources and implementation of programs intended to achieve progress towards these metrics. We explore ways to localize global goals to best support human well-being and environmental health by systematically comparing the UN Sustainable Development Goals (SDGs) with regionally-derived well-being dimensions that encompass components of social–ecological resilience across the Pacific Islands. Our research shows that, in the context of the Pacific, there are overlaps but also significant gaps between regional conceptions of well-being and the globally-derived SDGs. Some dimensions, related to human health and access to infrastructure and finances, are well represented in the SDGs. Other dimensions of high importance when localizing perspectives of well-being, such as those regarding connections between and across people and place and Indigenous and local knowledge, are not. Furthermore, internationally generated indicators may result in trade-offs and measurement challenges in local contexts. Creating space for place-based values in global sustainability planning aligns with international calls for transformational changes needed to achieve global goals. We identify challenges in applying SDG indicators at the local level and provide lessons learned to foster equitable and holistic approaches and outcomes for sustainability.

Investigating the Role of Fish and Fishing in Sharing Networks to Build Resilience in Coral Reef Social-Ecological Systems - Rachel Dacks; Tamara Ticktin; Stacy D. Jupiter; Alan M. Friedlander (Coastal Management, 2020)

Linkages between measures of biodiversity and community resilience in Pacific Island agroforests - Tamara Ticktin; Shimona Quazi; Rachel Dacks; Mesulame Tora; Ashley McGuigan; Zoe Hastings; Alivereti Naikatini (Conservation Biology, 2018)
Designing agroecosystems that are compatible with the conservation of biodiversity is a top conservation priority. However, the social variables that drive native biodiversity conservation in these systems are poorly understood. We devised a new approach to identify social–ecological linkages that affect conservation outcomes in agroecosystems and in social‐ecological systems more broadly. We focused on coastal agroforests in Fiji, which, like agroforests across other small Pacific Islands, are critical to food security, contain much of the country's remaining lowland forests, and have rapidly declining levels of native biodiversity. We tested the relationships among social variables and native tree species richness in agroforests with structural equation models. The models were built with data from ecological and social surveys in 100 agroforests and associated households. The agroforests hosted 95 native tree species of which almost one‐third were endemic. Fifty‐eight percent of farms had at least one species considered threatened at the national or international level. The best‐fit structural equation model (R 2 = 47.8%) showed that social variables important for community resilience—local ecological knowledge, social network connectivity, and livelihood diversity—had direct and indirect positive effects on native tree species richness. Cash‐crop intensification, a driver of biodiversity loss elsewhere, did not negatively affect native tree richness within parcels. Joining efforts to build community resilience, specifically by increasing livelihood diversity, local ecological knowledge, and social network connectivity, may help conservation agencies conserve the rapidly declining biodiversity in the region.